Caracterização, avaliação da bioatividade in vitro e da neoformação óssea in vivo de materiais cristalinos dopados com íons estrôncio - Pessôa, Joyce Andreza Moreira (2014)
The search for ideal bone grafts drives the production of new osteoconductive and osteocutaneous biomaterials. Crystalline materials doped with strontium ion (Sr2+) may be an alternative for bone regeneration of critical size defects. The objective of this study was to characterize, evaluate the in vitro bio-reactivity and in vivo bone neoformation potential of Sr2+ doped crystalline materials. The crystalline powder (CP), similar to the bioactive glass (BG) S53P4 and modified with Sr2+, was produced via sol-gel route and heat treated at 800 ºC. To include Sr 2+ in the CP, there was a molar substitution of 12.5 % or 25 % of calcium oxide (CaO) by strontium oxide (SrO). Three crystalline materials were used: CP without Sr2+ (CPSr0), CP with 12.5 % Sr2+ (CPSr12.5) and CP with 25 % Sr2+ (CPSr25). The chemical composition of the CP (CPSr0, CPSr12.5 and CPSr25) was analyzed by energy dispersive x-ray (EDX). The release profile of Sr2+ in distilled water (1, 6 and 12 hours) was obtained by flame atomic absorption spectroscopy (FAAS). The bioreactivity was evaluated in vitro by immersion in simulated body fluid (SBF) (24, 72 and 168 hours) and analyzed by X-ray diffraction (XRD). In the in vivo test, 2 critical defects of 7 mm in diameter were performed on the calvarium of male Wistar rats, totaling 30 defects, which were randomly distributed in the groups: (1) Negative control - blood clot; (2) Test 1 - CPSr0; (3) Test 2 - CPSr25. The evaluations were performed in the 14 and 28 postoperative days with the sample number per group in each period of four for the computerized microtomography (micro-CT) and five for the histological analysis. Doping with Sr2+ was confirmed by the presence of SrO in the percentages of 2.209 % and 6.929 % for CPSr12.5 and CPSr25. The release values of Sr2+ of CPSr25 were higher, with increasing behavior until the time of 6 hours and small slope in 12 hours. Characteristic peaks of hydroxyapatite (HA) (26 º, 32 º, 40 º, 45 º, 50 º and 56 º) were determined in the samples after bioactivity analysis. In the 168 hour period, higher HA peaks (26 ° and 32 °) were observed in the CP without Sr2+. The micro-CT and histomorphometry of the samples obtained from the in vivo test showed that CPSr25 was statistically different and higher than CPSr0 for bone volume (p = 0.016), percentual bone volume (p = 0.016) and new bone formation (p = 0.025) at 28 days indicating that Sr2+ doping has a greater potential for bone regeneration. In the histological analysis of the CPSr25 group, it was observed higher values for the degree of vascularization at 28 days when compared to CPSr0 (p = 0.003). In conclusion, CP were successful in the doping process and ionic release of Sr2+ observed through EDX e FAAS. The main HA peaks showed lower values for CP with Sr2+ in the time of 168 hours. The substitution of CaO by SrO presented better results in the repair of critical defects from the microtomographic and histological point of view. These data confirm that doping of biomaterials with Sr2+ ions is a good strategy for use as bone substitutes in the healing of critical defects.